(untitled) (Scientific journal of the Fergana State University, 2024)
The article traces the creation and development of the oil industry in the Fergana region during the Russian Empire. Based on archival materials and other historical sources, the author reflects on the purpose of the organization of this branch of industry, the achievements and existing shortcomings, and their status.